Distributed systems - Mullender, Sape J. (ACM Press frontier series, 1993)
Technological progress in distributed computing systems continues at a rapid pace, and this second edition has been completely revised to reflect the current state of the art. Examples and case studies of commericial and experimental systems are provided by a distinguished author team, whose work reflects the cutting edge of modern developments in the field.